2021
DOI: 10.1097/corr.0000000000001751
|View full text |Cite
|
Sign up to set email alerts
|

Does Medical Students’ Sense of Belonging Affect Their Interest in Orthopaedic Surgery Careers? A Qualitative Investigation

Abstract: Background The concept of social belonging has been shown to be important for retention and student success in collegiate environments and general surgery training. However, this concept has never been explored in relation to medical students’ impressions of orthopaedic surgery careers. Question/purpose To investigate medical students’ sense of belonging in orthopaedic surgery and how it affects their interest in pursuing orthopaedic surgery careers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 33 publications
0
53
0
1
Order By: Relevance
“…8 It has been shown that medical students are more likely to pursue orthopaedics if they see themselves as having the same traits as the traditional 'white, athletic, male' orthopaedic surgeon. 9 However, diversity has repeatedly been shown to improve innovation and patient outcomes, [10][11][12] so we need to work harder to make a career in orthopaedics accessible to all.…”
mentioning
confidence: 99%
“…8 It has been shown that medical students are more likely to pursue orthopaedics if they see themselves as having the same traits as the traditional 'white, athletic, male' orthopaedic surgeon. 9 However, diversity has repeatedly been shown to improve innovation and patient outcomes, [10][11][12] so we need to work harder to make a career in orthopaedics accessible to all.…”
mentioning
confidence: 99%
“…Previous studies have evaluated the impact of experiences in youth through medical school that result in the decisions of women to pursue careers in orthopaedic surgery [3,11,22,25]. This decision is often informed by what they observe in the experiences of women in training as well as longstanding stereotypes that can affect feelings of belonging [8]. The environment faced by women while in medical and surgical training programs has been documented [18] and impacts not only the opinions of students regarding the field but also the wellbeing of women residents.…”
Section: Discussionmentioning
confidence: 99%
“…The perceived experiences of women residents in orthopaedic surgery and the stereotypes of the specialty and people in orthopaedic surgery can influence a medical student's belonging in and desire to pursue a career in orthopaedic surgery [8,11], and the slow growth in gender diversity in orthopaedic surgery has been attributed, in part, to these perceptions. One study surveyed medical students and found that perceptions of long hours, high physical demands, and the predominance of men in the field were deterrents to pursuing careers in orthopaedic surgery for women [2].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Gerull et al on medical students’ sense of belonging revealed that students held stereotypes about orthopaedic surgeons and derived a sense of belonging from how closely their identities aligned with these stereotypes. Students who experienced a lack of identity alignment felt like they were in a cultural “out-group.” 1 Additionally, the “out-group” students reported that their peer interactions with the “in-group” negatively affected their perception of orthopaedics because of their exclusionary attitude 1 . Fortunately, another study found that underrepresented minority (URM) students who perceived orthopaedics as less diverse and inclusive changed their mind after an orthopaedic rotation 2 .…”
Section: Challenges Facing Lgbtq+ Orthopaedic Surgeonsmentioning
confidence: 99%